2010
DOI: 10.1103/physrevb.81.041401
|View full text |Cite
|
Sign up to set email alerts
|

Many-body instability of Coulomb interacting bilayer graphene: Renormalization group approach

Abstract: Low-energy electronic structure of ͑unbiased and undoped͒ bilayer graphene consists of two Fermi points with quadratic dispersions if trigonal warping is ignored. We show that short-range ͑or screened Coulomb͒ interactions are marginally relevant and use renormalization group to study their effects on low-energy properties of the system. We find that the two quadratic Fermi points spontaneously split into four Dirac points. This results in a nematic state that spontaneously breaks the sixfold lattice rotation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
376
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(396 citation statements)
references
References 23 publications
18
376
2
Order By: Relevance
“…We considered a single-particle picture in order to provide a simple description of a broad range of features. Depending on sample quality, electron-electron interactions also contribute to symmetry breaking and Landau level splitting, [67][68][69][70][71][72][73][74][75][76][77][78][79] as does interlayer asymmetry due to the presence of an external gate or doping. 28,31,42,45,[80][81][82] Nevertheless, an experimental observation of features related to next-nearest layer couplings should be possible in high-mobility samples including suspended graphene 69,[83][84][85][86] or graphene on a boron nitride substrate.…”
Section: Discussionmentioning
confidence: 99%
“…We considered a single-particle picture in order to provide a simple description of a broad range of features. Depending on sample quality, electron-electron interactions also contribute to symmetry breaking and Landau level splitting, [67][68][69][70][71][72][73][74][75][76][77][78][79] as does interlayer asymmetry due to the presence of an external gate or doping. 28,31,42,45,[80][81][82] Nevertheless, an experimental observation of features related to next-nearest layer couplings should be possible in high-mobility samples including suspended graphene 69,[83][84][85][86] or graphene on a boron nitride substrate.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Detailed tight-binding-model studies showed that inclusion of next-neighbor interlayer coupling changes the band structure in the bilayer, producing a Lifshitz transition in which the isoenergetic line about each valley is broken into four pockets with linear dispersion. 2,23 At energies higher than 1 meV the four pockets merge into one pocket with the usual quadratic dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, electron-electron interactions might result in further energy spectrum transformation, where the number of low-energy cones can be reduced to 2 near each of the two K points. 18,19 In this case the minimum conductance of the bilayer graphene is supposed to be increased comparing to a bilayer with parabolic dispersion (8e 2 /h). This scenario was also supported by experimental results on suspended bilayer graphene in which strong spectrum reconstructions and electron topological transitions were observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Explicit examples are tightbinding models on checkerboard and kagome lattices, respectively [9,13]. Topological quadratic Fermi points also appear in physical systems such as bilayer graphene [14][15][16][17][18][19], photonic crystals [20], oxide heterostructures [21], and surface state of topological insulators [22].…”
mentioning
confidence: 99%